Operational tolerance after intestine re‐transplantation in childhood and immunological correlates. Case report and review. (18th December 2022) - Remaley, Lisa; Ashokkumar, Chethan; Soltys, Kyle A.; Mazariegos, George Vincent; Bond, Geoffrey James; Khanna, Ajai; Ganoza, Armando; Reyes‐Mugica, Miguel; Zeevi, Adriana; Sindhi, Rakesh
Abstract: Background: Operational tolerance after retransplantation of the intestine has never been reported. Purpose: To two recently described intestine transplant recipients with operational tolerance, we now add a third. Methods: Review of case record and immunological testing to confirm donor‐specific hyporesponsiveness in multiple immune cell compartments. Results: Re‐transplanted with a multivisceral liver‐ and kidney‐inclusive intestine allograft at age 12 years, this recipient self‐discontinued immunosuppression 14 years after the retransplant and has been rejection free for 2 years thereafter. As in the two previous reports, immunological testing demonstrated decreased donor‐specific inflammatory response of T‐cytotoxic memory cells and B‐cells, decreased presentation of donor antigen by B‐cells and monocytes, absence of donor‐specific anti‐HLA antibodies, circulating FOXP3 + T‐helper cells, and intact cellular and humoral immunity to cytomegalovirus and Epstein–Barr virus. Additionally, our recipient demonstrated enhanced donor‐activation‐induced apoptosis of alloreactive T‐cytotoxic memory cells. Conclusions: Despite variable paths to tolerance which include graft versus host disease in two previous cases, and rejection‐related loss of the primary isolated intestinal allograft in our recipient, the three cases with operational tolerance are bound by common themes: a relatively large donor antigenic load transmitted during intestine transplantation, and donor‐specific hyporesponsiveness. Cell‐based assays suggest enhanced donor‐induced apoptosis of recipient T‐cells and circulating T‐regulatory cells as mechanistic links between antigenic load and donor‐specific hyporesponsiveness.